Analysis of Students’ Scientific Literacy Abilities on Science Learning in High School - Ayu Rahmi; Syarifah Rita Zahara; Sirry Alvina; M. Ridwan Fadli; Eka Juliana (LPPM Universitas Malikussaleh, 2024)
The world of education plays an important role in civilization and the mobility of future generations. However, there are still weaknesses in the learning process, especially in methods that are monotonous and rely on memorization, which results in students having difficulty relating learning to real contexts. Science learning in schools emphasizes results, while the process is often neglected. Scientific literacy, which includes content, context, competencies and attitudes, is the focus of this research to improve students' scientific literacy abilities at the high school level. Data from the Program for International Students Assessment (PISA) shows that scientific literacy in Indonesia is still low. This research aims to analyze students' scientific literacy profiles. Data collection was carried out through scientific literacy questions that were validated constructively and empirically. The scientific literacy indicators measured include 1) Identifying valid scientific opinions; 2) Understanding of research design elements and their influence on findings; 3) Ability to complete tests or questions related to scientific phenomena; 4) Understanding and interpreting basic statistics; 5) Ability to draw conclusions, observe and make decisions based on data. Students' scientific literacy abilities are divided into very good, good, sufficient and poor categories. Based on the research results, it was found that the percentage of students in the very good category was 27.08%, in the good category was 31.25%, in the fair category was 36.45%, and in the low category was 5.20%. Based on these results, it can be concluded that the highest percentage describing students' scientific literacy abilities is at sufficient criteria. Therefore, it is important to increase students' scientific literacy.